Multifunctional perennial production systems for bioenergy: performance and progress. Issue 5 (11th May 2020) - Englund, Oskar; Dimitriou, Ioannis; Dale, Virginia H.; Kline, Keith L.; Mola‐Yudego, Blas; Murphy, Fionnuala; English, Burton; McGrath, John; Busch, Gerald; Negri, Maria Cristina; Brown, Mark; Goss, Kevin; et al.
Abstract: As the global population increases and becomes more affluent, biomass demands for food and biomaterials will increase. Demand growth is further accelerated by the implementation of climate policies and strategies to replace fossil resources with biomass. There are, however, concerns about the size of the prospective biomass demand and the environmental and social consequences of the corresponding resource mobilization, especially concerning impacts from the associated land‐use change. Strategically integrating perennials into landscapes dominated by intensive agriculture can, for example, improve biodiversity, reduce soil erosion and nutrient emissions to water, increase soil carbon, enhance pollination, and avoid or mitigate flooding events. Such "multifunctional perennial production systems" can thus contribute to improving overall land‐use sustainability, while maintaining or increasing overall biomass productivity in the landscape. Seven different cases in different world regions are here reviewed to exemplify and evaluate (a) multifunctional production systems that have been established to meet emerging bioenergy demands, and (b) efforts to identify locations where the establishment of perennial crops will be particularly beneficial. An important barrier towards wider implementation of multifunctional systems is the lack of markets, or policies, compensating producers for enhanced ecosystem services and other environmental benefits. This deficiency is particularly important since prices for fossil‐based fuels are low relative to bioenergy production costs. Without such compensation, multifunctional perennial production systems will be unlikely to contribute to the development of a sustainable bioeconomy. This article is categorized under: Bioenergy > Systems and Infrastructure Bioenergy > Climate and Environment Energy Policy and Planning > Climate and Environment Abstract : Seven different cases in different world regions are here reviewed to exemplify and evaluate (a) establishment of multifunctional production systems to meet emerging bioenergy demands, and (b) efforts to identify specific locations where the establishment of perennial crops will be particularly beneficial